2007
DOI: 10.1182/blood-2006-06-028175
|View full text |Cite
|
Sign up to set email alerts
|

HIV modulates the expression of ligands important in triggering natural killer cell cytotoxic responses on infected primary T-cell blasts

Abstract: The ability of natural killer (NK) cells to kill virus-infected cells depends on the presence of ligands for activation receptors on the target cells. We found the presence of few, if any, NKp30 and NK46 ligands on T cell blasts infected with HIV, although NKp44 ligands were found on infected cells. HIV does induce the NKG2D ligands ULBP-1, -2, and -3. These ligands are involved in triggering NK cells to kill autologous HIV-infected cells, because interfering with the interaction between NKG2D, but not NKp46, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
198
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(214 citation statements)
references
References 58 publications
10
198
2
1
Order By: Relevance
“…Reductions in NKp46 expression in HIV-unrelated in vitro experiments was demonstrated to occur upon activation and, in some cases, after direct ligation of the receptor (30,39). However, infection of CD4 + T lymphocytes with HIV does not induce the expression of NKp46 ligands (31). As such, ligation-induced downregulation is unlikely to explain the altered patterns of NKp46 expression observed on NK cells from HIV-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reductions in NKp46 expression in HIV-unrelated in vitro experiments was demonstrated to occur upon activation and, in some cases, after direct ligation of the receptor (30,39). However, infection of CD4 + T lymphocytes with HIV does not induce the expression of NKp46 ligands (31). As such, ligation-induced downregulation is unlikely to explain the altered patterns of NKp46 expression observed on NK cells from HIV-infected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, this raises the conundrum of how NKp46 expression is decreased on NK cells during HIV infection. Indeed, the expression of NKp46 ligands is not induced in CD4 + T lymphocytes upon HIV infection (31). As such, the direct activation of NK cells through NKp46 cannot explain the decreased expression of NKp46 observed during chronic HIV infection.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…One plausible such mechanism is the expression of a natural killer (NK) ligand on CD4 ϩ T cells during HIV infection: we (6) demonstrated that NKp44L, the ligand of NKp44 NK receptor, is expressed on CD4 ϩ T cells of HIV-infected patients and showed that cells expressing NKp44L are highly sensitive to NK lysis. Ward et al (7) have recently confirmed the specific expression of NKp44L on CD4 ϩ T cells after in vitro infection with HIV-1.…”
mentioning
confidence: 84%
“…NKp44 cellular ligand (NKp44L) is expressed on uninfected CD4 + T cells during an HIV infection, correlating with the loss of CD4 + T cells and increase of viral load (Vieillard et al, 2005). NKp44L is only expressed in high amounts on uninfected CD4 + T cells and is not responsible for inducing NK lysis of HIV-infected cells (Ward et al, 2007). To avoid NK killing of HIV infected CD4 + T cells, the Nef protein of HIV-1 retains NKp44L intracellularly, preventing cell surface expression and interaction with NKp44 (Fausther-Bovendo et al, 2009).…”
Section: A Hallmark Of Hiv Infection Is the Progressive Depletion Of Cd4mentioning
confidence: 99%